A signal sequence suppressor mutant that stabilizes an assembled state of the twin arginine translocase - Huang, Q; Alcock, F; Kneuper, H; Deme, J; Rollauer, S; Lea, S; Berks, B; Palmer, T (National Academy of Sciences, 2017)
The twin-arginine protein translocation (Tat) system mediates transport of folded proteins across the cytoplasmic membrane of bacteria and the thylakoid membrane of chloroplasts. The Tat system of Escherichia coli is made up of TatA, TatB and TatC components. TatBC comprise the substrate receptor complex, and active Tat translocases are formed by the substrate-induced association of TatA oligomers with this receptor. Proteins are targeted to TatBC by signal peptides containing an essential pair of arginine residues. We isolated substitutions, locating to the transmembrane helix of TatB that restored transport activity to Tat signal peptides with inactivating twin arginine substitutions. A subset of these variants also suppressed inactivating substitutions in the signal peptide binding site on TatC. The suppressors did not function by restoring detectable signal peptide binding to the TatBC complex. Instead, site specific crosslinking experiments indicate that the suppressor substitutions induce conformational change in the complex and movement of the TatB subunit. The TatB F13Y substitution was associated with the strongest suppressing activity, even allowing transport of a Tat substrate lacking a signal peptide. In vivo analysis using a TatA-YFP fusion showed that the TatB F13Y substitution resulted in signal peptide independent assembly of the Tat translocase. We conclude that Tat signal peptides play roles in substrate targeting and in triggering assembly of the active translocase.